Carboplatin and Pembrolizumab Chemoimmunotherapy Achieves Remission in Recurrent, Metastatic Sebaceous Carcinoma. Issue 5 (September 2018) - Kodali, Saranya; Tipirneni, Eswar; Gibson, Pamela C.; Cook, Deborah; Verschraegen, Claire; Lane, Katherine A.
Abstract : A 72-year-old Caucasian woman who had recurrent sebaceous carcinoma of the right orbit with bilateral cervical lymph node involvement 24 months after orbital exenteration was treated with carboplatin (area under the curve of 5) and pembrolizumab (2 mg/kg) for 6 cycles, followed by maintenance pembrolizumab. She obtained a complete pathological remission and remains free of local, regional, and systemic disease at 15 months. Abstract : The authors discuss an aggressive recurrence and metastasis of orbital sebaceous carcinoma treated with the chemoimmunotherapy combination carboplatin and pembrolizumab, an antiprogrammed death-1 immunotherapeutic.